Graviton self-energy from gravitons in cosmology*This paper is dedicated to Stanley Deser on the occasion of his 90th birthday. (17th June 2021) - Tan, L; Tsamis, N C; Woodard, R P
Abstract: Although matter contributions to the graviton self-energy − i [ Σ ρ σ μ ν ] ( x ; x ′ ) must be separately conserved on x μ and x ′ μ, graviton contributions obey the weaker constraint of the Ward identity, which involves a divergence on both coordinates. On a general homogeneous and isotropic background this leads to just four structure functions for matter contributions but nine structure functions for graviton contributions. We propose a convenient parameterization for these nine structure functions. We also apply the formalism to explicit one loop computations of − i [ Σ ρ σ μ ν ] ( x ; x ′ ) on de Sitter background, one of the contributions from a massless, minimally coupled scalar and the other for the contribution from gravitons in the simplest gauge. We also specialize the linearized, quantum-corrected Einstein equation to the graviton mode function and to the gravitational response to a point mass.